Increasing nurses' occupational well-being: the role of career shocks, job crafting and supervisor autonomy support - Ying Zhang; Xing Bu; Na Zhang (BMC, 2024)
Abstract Background This study aims to explore the influence of career shocks on nurses' occupational well-being through job crafting and the moderating role of supervisor autonomy support. Method The present study used a cross-sectional design. And the study included 714 frontline nurses in China, and we used structural equation modelling (SEM) to test our hypotheses. Results Job crafting mediated both the relationship between positive career shocks and occupational well-being and the relationship between negative career shocks and occupational well-being. Supervisor autonomy support moderated the indirect relationships. Conclusions Positive and negative career shocks could increase and impair nurses' occupational well-being through job crafting, respectively. We contribute to helping nurses make sense of career shocks and preparing for career shocks, and hospital administrators and nurses' direct supervisors can help nurse better cope with career shocks in attending job crafting activities and providing more autonomy supports.